Assessment of biceps brachii and upper trapezius muscle fatigue using EMG measurements - Dawal, S. Z.; Soin, N.; Ali, N.; Mahadi, W. N. W.; Ismail, Z.; Aziz, S. A. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/